Effect of date of sowing, nitrogen levels and spacing on growth and yield of ajwain (Trachyspermum ammi (L.) Sprague) - G C Yadav, Prem Nath, R C Jaiswal, R B Verma (Journal of Spices and Aromatic Crops, 2008)
The effect of three dates of sowing (15th October, 30th October and 14th November), four levelsof nitrogen (0, 20, 40 and 60 kg ha-1) and three spacings (30 cm x 10 cm, 30 cm x 20 cm and 30cm x 30 cm) on growth and yield of ajwain (Trachyspermum ammi) was studied at Kumarganj(Uttar Pradesh). Sowing on 30th October significantly increased plant height, number ofprimary and secondary branches plant-1, plant spread, number of umbels plant-1, number ofumbellets umbel-1, number of seeds plant-1 and yield of seeds plant-1 and ha-1. Maximumvalues of all the parameters were obtained with application of 60 kg N ha-1. Wider spacing(30 cm x 20 cm and 30 cm x 30 cm) was found to be effective for all the characters except seedyield, which was higher at the closest spacing (30 cm x 10 cm). The interaction of dates ofsowing and nitrogen levels significantly increased primary and secondary branches plant-1as well as seed yield ha-1.